Recent Advances in Green Analytical Chemistry - Khairmode, Payal R.; Darade, Ramdas B. (Asian Journal of Pharmaceutical Research and Development, 2025)
This review article provides a comprehensive overview of the development and validation of a UV-Spectroscopic method for the quantification of Ziprasidone Hydrochloride (HCl) in both bulk and marketed formulations. Ziprasidone HCl, an atypical antipsychotic used in the treatment of schizophrenia and bipolar disorder, requires precise analytical methods for its quantification due to its clinical importance. The study emphasizes the methodological aspects, including the selection of solvents, determination of the maximum absorbance wavelength (λmax), and the preparation of standard solutions. The validation process covers key parameters such as linearity, accuracy, precision, specificity, and sensitivity. The method's specificity is confirmed by the lack of interference from common excipients. This UV spectroscopic method is concluded to be simple, reliable, cost-effective, and suitable for routine quality control analysis of Ziprasidone HCl in pharmaceutical preparations. The article also includes a review of the latest literature on analytical methods for Ziprasidone HCl, highlighting recent advancements and comparisons with other techniques such as HPLC.